Implementation of the Policy to Strengthen the Role of the Sharia Supervisory Board at the Financial Services Authority on Governance of Sharia Rural Banks - R Jono Subiyanto; Yahya Rachmana Hidayat; Deddy Supriady Bratakusumah; Surryanto Djoko Waluyo; Harits Hijrah Wicaksana (Dinasti Publisher, 2025)
The role of the Sharia Supervisory Board (Dewan Pengawas Syariah, DPS) is a crucial element in maintaining compliance with sharia principles and strengthening the governance of Sharia people’s Economy Banks (Sharia BPRs). The background to this research stems from the issuance of Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (UU P2SK), which places the DPS on an equal footing with directors and commissioners. This provision is expected to strengthen the institutional sharia supervisory function and increase the effectiveness of the implementation of sharia principles in the banking sector. However, this change in position also poses new challenges, including independence, limited resources, concurrent positions, and remuneration disparities for DPS members. This research aims to analyze the implementation of the DPS regulatory policy in the UU P2SK Law on the governance of Sharia BPRs and examine how this equalization of positions is interpreted as a form of strengthening the DPS 's role. The research uses a descriptive qualitative method through literature review, observation, and in-depth interviews with five informants consisting of the Financial Services Authority (OJK), the association of Sharia Rural Banks Throughout Indonesia (HIMBARSI), and Sharia BPRs. By using policy implementation analysis based on Grindle’s theory, the research results show that the policy of strengthening the DPS has a positive impact on increasing legitimacy, public trust, and the effectiveness of sharia governance. However, successful implementation is still influenced by management commitment, institutional capacity, and support from the Financial Services Authority (OJK) and the National Sharia Council (DSN-MUI). Optimizing the role of the DPS requires appropriate remuneration, restrictions on concurrent positions, and ongoing support to ensure the integrity and sustainability of sharia governance.